To Analyze Idiom Used in Selected Song Lyrics of Birds of a Feather by Billie Eilish - Fathimah Az Zahro; Otong Setiawan Djauhari (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to analyze the idiomatic expressions found in the song lyrics of “Birds of a Feather” by Billie Eilish. Idioms are an essential part of figurative language that enriches the meaning of lyrics and contributes to the emotional and cultural depth of a song. Using a qualitative descriptive method, this research identifies and classifies the idioms based on Makkai’s (1972) typology and interprets their contextual meanings through Leech’s (1981) theory of semantics. The analysis reveals various types of idioms, including phrasal verb idioms and tournure idioms, that reflect themes of emotional connection and loyalty. The findings demonstrate how idioms enhance lyrical expression and offer deeper insight into the artist’s intended message. This study contributes to the understanding of idiomatic usage in contemporary music and provides a linguistic perspective on lyrical interpretation.